The Influence of Price on Tourists' Purchase Interest at Aloft Bali Seminyak - Satriaadi, Komang Yogi Satriaadi; Wiartha, Nyoman Gede Mas; Jata, I Wayan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the effect of price on purchase intention. This type of research is quantitative with a population of foreign and domestic tourists who know Aloft Bali Seminyak. The sample used was 100 respondents. The sampling method used was purposive sampling. The data analysis technique used was simple linear regression analysis with SPSS version 29 for Windows. The results of this study indicate that Price (X) has a significant effect on Purchase Intention (Y) with a calculated t value> t table = 17.580> 1.984 and a significance value <???? = 0.001 <0.05. It can be concluded from the results of this study that Price has a positive and significant effect on Purchase Intention at Aloft Bali Seminyak.